Impact of cognitive reserve on the progression of mild cognitive impairment to Alzheimer's disease in Japan. Issue 4 (15th April 2014) - Osone, Akira; Arai, Reiko; Hakamada, Rina; Shimoda, Kazutaka
<x xml:space="preserve">Abstract</x> Aim The present study aimed to investigate whether cognitive reserve (CR), referring here to education and premorbid intelligence (IQ), is associated with the risk for progression from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Methods A total of 51 patients with MCI and 59 patients with AD were prospectively enrolled for assessment with the Mini‐Mental State Examination, the Japanese version of the cognitive subscale of the Alzheimer's Disease Assessment Scale, the Japanese version of the Nelson Adult Reading Test (JART), magnetic resonance imaging (MRI) and single‐photon emission computed tomography (SPECT), adjusting for sex, age at diagnosis, age at onset and duration of illness. Results SPECT findings showed hypoperfusion in the posterior cingulate gyri and precunei, suggesting that the participants were in the early or mild stage of AD or MCI. Voxel‐based morphometry MRI showed no statistical differences between the two groups in gray matter loss in the entorhinal and hippocampal areas; however, multiple logistic regression analysis showed a significant difference in premorbid IQ measured with JART. Conclusion Despite the limitations of the cross‐sectional design, the findings suggest that premorbid intellectual function might explain the discrepancy in clinical status between MCI and AD patients with a similar magnitude of brain pathology and comorbid medical disorders. Geriatr Gerontol Int 2015; 15: 428–434.